ANALYSIS OF URBAN REGIONAL PLANNING USE EX-HGU PTPN III LAND USING SIANTAR MARTOBA DISTRICT - Uswatun Hasanah (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2020)
Utilization of PTPN III Ex-HGU Land in Siantar Martoba Sub district has an area of 573.42 Ha with the largest land use being in Tanjung Pinggir Sub-District with utilization area of 487.40 Ha. PTPN III's Ex-HGU Land Use Analysis was analyzed using the highest and best land use analysis through 3 of them: Physical aspects referring to SNI-03-1733-2004 regarding the procedures for planning the urban environment, Legality aspects, and cost aspects involving Local Government Organizations in the Focus Discussion Group. The results of the analysis can be concluded that the Utilization of the Ex-HGU Land of PTPN III is planned in 3 (three) stages for 15 years namely: Phase I (2020-2024) Settlement and Industrial Areas, Phase II (2025-2029) of Industrial and Trade Industrial Areas, and Public Facilities Area, Phase III (2030-2034) Settlement and Environmental Areas I, Settlement and Environmental Areas II with a total planning cost of IDR 2.936.816.327.250. In the planning of PTPN III's ex-HGU land, it not only determines land use planning but also involves several stakeholders, namely government institutions, both central and regional with all ranks, private institutions as users of the area, as well as the community as the development, community as actors of development (stakeholders) also as the owner of the development (shareholder).